Phase transitions in neutron star equation of state induced by the delta resonances matter. Issue 5 (April 2016) - J C T, Oliveira; Rodrigues, H; Duarte, S B
Abstract: In the present work we determine the equation of state and the population of baryons and leptons, and also we discuss the implication of changes in the baryon-meson coupling constants to the formation of delta matter in the stellar medium. And also in this work the phase transition is explored with respect to the domain of the delta-mesons coupling constants.